2015
DOI: 10.3390/f6082853
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Landscape Locations along Trails Based on Walking Experiences and Distances Traveled in the Akasawa Forest Therapy Base, Central Japan

Abstract: Forest planners are interested not only in forest spaces that visitors prefer but also in the preferred spatial arrangements of landscape features. In this study, we aimed to clarify walkers' evaluations of four landscape locations composed of various scenic features in various spatial arrangements along forest walking routes. We also analyzed the trends, differences, and common features associated with different walking distances and experiences. The results are summarized as follows: (1) The walkers' evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Although few studies have focused on this issue, studies about forest bathing suggested that the significant effect on mental restoration also accompanied by hard-wood species of oak (Park et al 2007, Lee et al 2009, Han et al 2016) and maple (Lee et al 2014, Song et al 2015b, Han et al 2016). In addition, more studies suggested that the forest bathing effect on anxiety alleviation was accompanied by coniferous tree species, such as Japanese cypress (Chamaecyparis obtusa) (Lee et al 2014, Song et al 2015a, Zhang et al 2015, Song et al 2016) and pine (Pinus spp.) (Sonntag-Öström et al 2015a, b, Chun et al 2016, Han et al 2016).…”
Section: Discussion the Employment Of Spring Time In Maymentioning
confidence: 99%
See 1 more Smart Citation
“…Although few studies have focused on this issue, studies about forest bathing suggested that the significant effect on mental restoration also accompanied by hard-wood species of oak (Park et al 2007, Lee et al 2009, Han et al 2016) and maple (Lee et al 2014, Song et al 2015b, Han et al 2016). In addition, more studies suggested that the forest bathing effect on anxiety alleviation was accompanied by coniferous tree species, such as Japanese cypress (Chamaecyparis obtusa) (Lee et al 2014, Song et al 2015a, Zhang et al 2015, Song et al 2016) and pine (Pinus spp.) (Sonntag-Öström et al 2015a, b, Chun et al 2016, Han et al 2016).…”
Section: Discussion the Employment Of Spring Time In Maymentioning
confidence: 99%
“…However, both oak and maple forests resulted in less perceived anxiety alleviation from employment than the birch forest. This may be caused by the visional view in the birch forest with easily accessible, open and bright settings with visible lake, which were all evaluated to be very attractive to visitors (Sonntag-Öström et al 2015b, Zhang et al 2015. Students may worry about their employment in the future before they went into the birch forest, but the forest bathing with specific view during their following minutes may have decreased some of the worry.…”
Section: The Difference Of Perceived Anxiety Alleviation Among Forestsmentioning
confidence: 99%
“…Self-report and psychophysical approaches have a high degree of flexibility and adaptability based on the perceptions and judgments of the lay public. However, they are usually used to assess FLQ that is case specific and on a small scale (e.g., forest parks or natural reserves) [4,[8][9][10][11][12][13][14]. In general, owing to the lack of appropriate data sources and evaluation criteria, no studies hitherto have assessed FLQ at the national level.…”
Section: Introductionmentioning
confidence: 99%
“…The situation is similar in other types of landscape or in landscapes where forest constitutes one of its components (Dudek, 2012) which means it is not examined from the inside, as a distinctive type of landscape. Conversely, a study assessing forest landscapes in Japan showed that it was surface waters that were the most important element enhancing landscape aesthetics (Zhang et al, 2015). Russian and Japanese research confirms that the most important element of landscapes for the Japanese is water, and for Russians topography (Petrova et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…By crossing the wall of forest we enter the interior of forest landscape. One of the main reasons why in many places worldwide people visit forests is the opportunity to enjoy attractive scenery (Hansson, Külvik, Bell, & Maikov, 2012;Paletto, Ferretti, Cantiani, & De Meo, 2012;Zhang et al, 2015;Tyrväinen, Silvennoinen, & Hallikaine, 2016). Due to these forest areas selected as a result of forest landscape assessment should be managed in ways making it possible to maintain or upgrade landscape value of the tree stands.…”
Section: Discussionmentioning
confidence: 99%